2016
DOI: 10.1007/s11095-016-1995-0
|View full text |Cite
|
Sign up to set email alerts
|

A Lower Temperature FDM 3D Printing for the Manufacture of Patient-Specific Immediate Release Tablets

Abstract: 2 ABSTRACTPurpose. The fabrication of a ready-to-use immediate release tablets via 3D printing provides a powerful tool to on-demand individualization of dosage form. This work aims to adapt a widely used pharmaceutical grade polymer, polyvinylpyrrolidone (PVP), for instant on-demand production of immediate release tablets via FDM 3D printing.Methods. Dipyridamole or theophylline loaded filaments were produced via processing a physical mixture of API (10%) and PVP in the presence of plasticizer through hot-mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
158
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(172 citation statements)
references
References 34 publications
6
158
1
7
Order By: Relevance
“…Amongst the different developed 3D printing technologies, fused deposition modeling (FDM) has several significant advantages such as low-cost manufacturing, the compatibility of using the combination of pharmaceutical grade polymers with APIs through hot-melt extrusion (HME) and the ability to fabricate hollow objects 1416 . Previous pharmaceutical researchers attempted to use FDM-based 3D printing mainly in fabricating drug delivery systems with immediate or controlled release characteristics 1719 , hot-melt extruding filaments of pharmaceutical grade polymers 15, 20, 21 , lowering printing temperatures 22 , and preparing personalized topical drug delivery together with 3D scanning 23 . To our knowledge, there is no report on the FDM based hollow tablets for intragastric floating sustained release (FSR) of drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Amongst the different developed 3D printing technologies, fused deposition modeling (FDM) has several significant advantages such as low-cost manufacturing, the compatibility of using the combination of pharmaceutical grade polymers with APIs through hot-melt extrusion (HME) and the ability to fabricate hollow objects 1416 . Previous pharmaceutical researchers attempted to use FDM-based 3D printing mainly in fabricating drug delivery systems with immediate or controlled release characteristics 1719 , hot-melt extruding filaments of pharmaceutical grade polymers 15, 20, 21 , lowering printing temperatures 22 , and preparing personalized topical drug delivery together with 3D scanning 23 . To our knowledge, there is no report on the FDM based hollow tablets for intragastric floating sustained release (FSR) of drugs.…”
Section: Introductionmentioning
confidence: 99%
“…However, materials availability for inkjet printing are limited, and efforts to broaden the materials range for biotechnology applications is an active area of AM research (Begines et al, 2016;He et al, 2016;Hart et al 2016;Saunders and Derby, 2014;Gudapati et al, 2016). In addition to inkjet 3D printing, other 3D printing technologies have shown significant progress (Alhnan et al, 2016;Goyanes et al, 2015;Khaled et al, 2015aKhaled et al, , 2015bOkwuosa et al, 2016;Sadia et al, 2016). Paste based extrusion printing (Khaled et al, 2015a(Khaled et al, , 2015b and fused deposition modelling (Goyanes et al, 2015;Okwuosa et al, 2016;Sadia et al, 2016) have demonstrated the potential of fabricating immediate and extended release dosage forms, as well as printing "polypills" which contain multiple actives (Goyanes et al, 2015;Khaled et al, 2015aKhaled et al, , 2015b, starting from approved pharmaceutical grade excipients.…”
Section: Introductionmentioning
confidence: 99%
“…Filament can be loaded with varying concentrations of drugs for specified doses by dissolving the drug in an ethanolic solution and submerging the unprinted, solid filament in the solution [53,54] . Filament can also be loaded with drugs by melting the filament and re-solidifying it after the addition of the drugs [55] . Once the 3D printed drug product is placed in vivo, the drug itself will diffuse out of the print, while the biodegradable filament will dissolve over time.…”
Section: Fused Deposition Of Solid Materialsmentioning
confidence: 99%